Implementation Of Deming Model On Tanjungpinang Onine Radio - Juliani Juliani; Arib Darlicza; Mu'alim Mu'alim; Putri Nadia Mahar Arini; Satriadi Satriadi (International Journal of Economics and Management Research, 2024)
The purpose of this study is to determine the extent of the implementation of performance management with the deming model at PT. Radio Diva Rubby Swarindo Onine Radio. The type of research used is descriptive research with a qualitative approach. This study used a purposive sample of 1 person, one of the staffing staff at Onine Radio. Implementation of performance management system at PT. Radio Diva Rubby Swarindo Onine Radio involves important elements such as planning, monitoring, communication, awarding, and performance appraisal. Supporting factors such as quality programming and positive interaction with listeners are key to a radio station's success. On the other hand, there are challenges that need to be overcome, including limited human resources, outdated facilities and infrastructure, and limited funding resources. With more effective efforts in implementing a performance management system, it is hoped that this radio station can continue to improve the quality of its broadcasts and satisfy listeners.